The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0247990
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic efficacy against Mycobacterium tuberculosis using ID93 and lipid-based adjuvant formulations in the mouse model

Abstract: An estimated 10 million people developed tuberculosis (TB) disease in 2019 which underscores the need for a vaccine that prevents disease and reduces transmission. The aim of our current studies is to characterize and test a prophylactic tuberculosis vaccine comprised of ID93, a polyprotein fusion antigen, and a liposomal formulation [including a synthetic TLR4 agonist (glucopyranosyl lipid adjuvant, GLA) and QS-21] in a preclinical mouse model of TB disease. Comparisons of the ID93+GLA-LSQ vaccines are also m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…AS01 was also included in the M72/AS01 tuberculosis subunit vaccine that gave high protection against disease progression in a phase 2b trial ( Tait et al, 2019 ). Recently, it was shown that liposomes containing MPL and QS21 potently enhanced the antibody response to recombinant SARS-CoV-2 RBD antigen in mice and rabbits ( Huang et al, 2020 ) and the addition of QS21 to a liposomal adjuvant (GLA-LS) formulated with tuberculosis recombinant poly-antigen ID93 enhanced IgG responses in mice ( Baldwin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…AS01 was also included in the M72/AS01 tuberculosis subunit vaccine that gave high protection against disease progression in a phase 2b trial ( Tait et al, 2019 ). Recently, it was shown that liposomes containing MPL and QS21 potently enhanced the antibody response to recombinant SARS-CoV-2 RBD antigen in mice and rabbits ( Huang et al, 2020 ) and the addition of QS21 to a liposomal adjuvant (GLA-LS) formulated with tuberculosis recombinant poly-antigen ID93 enhanced IgG responses in mice ( Baldwin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyinosinic-polycytidylic acid (Poly(I:C)) was obtained from InvivoGene. GLA-LSQ was provided by the Infectious Disease Research Institute (IDRI) and liposomal formulations of GLA were prepared as previously published ( Baldwin et al., 2021 ). Rehydragel was provided by the NIAID.…”
Section: Methodsmentioning
confidence: 99%
“…Polyinosinic-polycytidylic acid (Poly(I:C)) was obtained from InvivoGene. GLA-LSQ was provided by the Infectious Disease Research Institute (IDRI) and liposomal formulations of GLA were prepared as previously published ( 93 ). Rehydragel was provided by the NIAID.…”
Section: Methodsmentioning
confidence: 99%